Caracterização do Xote e do Baião dançados no interior do Estado de São Paulo - de Quadros Junior, Antonio Carlos [UNESP]; Fontes, Ellen Cristina; Dias, Romualdo [UNESP]; Volp, Catia Mary (Universidade Federal do Rio Grande do Sul (UFRGS), Escola de Educação Física, 2009)
Ballroom dance and Forro are part of Brazilian culture, and Xote and Baiao are part of Forro. The aim of this study was to diagramate the dances Xote and Baiao they are danced inside São Paulo State and to describe rhythmly these movements. It was observed and filmed several college couples dancing Xote and Baiao for analysis and description of the movements of the dances, by a discursive way and by diagrams. It was identified two basic structures ("Lateral Basic Step" and "Forward and Back Basic Step"), and variation steps "Open" and "Change of places with Turn", very used by couples.
Characterization of the Xote and Baiao danced inside the São Paulo State
Keywords: Dancing; Folklore; Music; Culture; Diagram